Palaeoenvironmental events and cycles at the southern front of the Tibetan Plateau during the Pleistocene: A record from lake sediments - Appel, Erwin; Goddu, Srinivasa R; Hu, Shouyun; Yang, Xiangdong; Wang, Suming; Igarashi, Yaeko; Gautam, Pitambar (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp.94-95